Rare bird documentation form for Bohemian Waxwing north of Redfield and north-northeast of Lamoni, 1984 and 1985 - Cummins, Raymond L.et al (1984)
Rare bird documentation form for one or more Bohemian Waxwings north of Redfield in Dallas County, IA on December 24, 1984 and a Bohemian Waxwing north-northeast of Lamoni in Decatur County, IA on January 20, 1985. Epson - sheet feed